CLASSIFICATION OF ORDINALS AND ITS FORMATION IN PASHTO (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
We can say that the numerals in Pashto represents one of the grammatical indicators that have not yet been fully formed. For this reason, some Pashto linguists have added it to the adjective category. In the literature on Pashto grammar, the spelling and even pronunciation of numerals differ markedly. Although it is true that this phenomenon is formed under the direct influence of existing dialects of the language, it requires a full scientific and research justification, a search for answers to many open questions within the framework of this topic. In this article, some issues related to ordinal numbers in Pashto will be analyzed.